A Distributed Adaptive Control Model for Microgrids with a Microservice-oriented Architecture. Issue 1 (1st December 2022) - Cao, Xiaoming; Zhang, Huabing; Shi, Hongyu
Abstract: In the face of increasingly complex application conditions, some distributed adaptive control models for microgrids suffer from large differences between voltage magnitudes and rated values. To address such shortcomings, a distributed adaptive control model for microgrids is designed for a microservice architecture. The mathematical expressions of the state integral control variables and control input variables under steady-state conditions are derived by extracting the integral control variables of the distributed generation units of the microgrid, and the current at the end of the line short circuit is used as the database to design the current quick-break protection mechanism for the microservice architecture. Experimental results is that the voltage magnitude of the distributed adaptive control model of the microgrid in the paper is 317.71V, which is closer to the rated output voltage value of 320V, indicating that the distributed adaptive control model of the microgrid is better when the microservice architecture is fully utilized.